2010
DOI: 10.1111/j.1757-5672.2009.00057.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Body Position on Defecation in Humans

Abstract: The results of the present study suggest that the greater the hip flexion achieved by squatting, the straighter the rectoanal canal will be, and accordingly, less strain will be required for defecation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 22 publications
1
35
0
1
Order By: Relevance
“…Maglinte et al suggested that evacuation in supine position with patients' legs extended and in protocols with just rest and strain sequences, does not precipitate the symptoms [20]. But in this study, with laying the patients in supine position and placing a pillow beneath the knees, a relative physiologic defecation position was created [21]. Also placing the hips in as much flexion as possible caused a relative relaxed position to make more perpendicular rectoanal canal.…”
Section: Mri Findings Indices (Pelvic Floor Motion Indices)mentioning
confidence: 99%
See 1 more Smart Citation
“…Maglinte et al suggested that evacuation in supine position with patients' legs extended and in protocols with just rest and strain sequences, does not precipitate the symptoms [20]. But in this study, with laying the patients in supine position and placing a pillow beneath the knees, a relative physiologic defecation position was created [21]. Also placing the hips in as much flexion as possible caused a relative relaxed position to make more perpendicular rectoanal canal.…”
Section: Mri Findings Indices (Pelvic Floor Motion Indices)mentioning
confidence: 99%
“…Also placing the hips in as much flexion as possible caused a relative relaxed position to make more perpendicular rectoanal canal. Hence, the strain could occur more easily and forcefully [21]. In addition if the procedures of MR defecography had been imposed a true sitting position with unusual circumstances that bothers the patients, so this imaging is not taken in a real physiologic defecation condition [22].…”
Section: Mri Findings Indices (Pelvic Floor Motion Indices)mentioning
confidence: 99%
“…Firstly, no physical contact with a squatting toilet is necessary. Secondly, the squatting position facilitates relaxation of the muscles around the anal canal and widens the anorectal angle to allow a straighter passage for defaecation [9]. This theory led to the use of a 'Defecation Posture Modi cation Device' (DPMD) with the seating type of toilet.…”
Section: Resultsmentioning
confidence: 99%
“…Appropriate management of excreta and wastewater disposal in sewerage systems is considered essential to public health policy [8]. Squatting toilets are common in Asian countries, and a squatting posture has been shown to widen the anorectal angle and facilitate defaecation [9]. However, use of a squatting toilet may be a concern if the toilet is left uncovered.…”
Section: Introductionmentioning
confidence: 99%
“…Third, whilst the RTA was examined in the left lateral position, the MRI sequence from which the anatomical models were delineated from was conducted in the supine position. Whilst there is evidence in the literature that hip flexion alters the anorectal angle [15] as well as the activity and functionality of the pelvic floor [16], there is little to none empirically quantifying the degree or nature of alteration in the left lateral position when compared with the standard supine position. The complexity of this issue is compounded by the fact that merely moving the position of the body from left lateral to supine, even without flexion of the hips, has in itself been found to significantly move some elements of the abdominal and pelvic anatomy [17,18].…”
Section: Discussionmentioning
confidence: 99%